2019
DOI: 10.12688/f1000research.16092.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding/managing trigeminal neuralgia

Abstract: Despite recent advances in understanding and treating trigeminal neuralgia, its management remains a considerable challenge. Better classification of different types of facial pain and the identification of prognostic factors for different treatment options lead the way toward better quality of life for the individual patient. Although the principles of treating trigeminal neuralgia remain basically the same, antiepileptic drugs, muscle relaxants, and neuroleptic agents are widely used medical treatment option… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 57 publications
1
36
0
3
Order By: Relevance
“…Patients on carbamazepine reported prominent treatment satisfaction (Jainkittivong et al 2012). The mean carbamazepine dose of the study participants was 691.8 mg, which is consistent with similar reports (Obermann 2019, Omoregie & Okoh, 2015, Bendtsen et al, 2019. We found that those patients who had history tooth extraction required a higher dose of carbamazepine compared to those without a history of tooth extraction.…”
Section: Association Between Treatment Satisfaction Level and Gendersupporting
confidence: 87%
“…Patients on carbamazepine reported prominent treatment satisfaction (Jainkittivong et al 2012). The mean carbamazepine dose of the study participants was 691.8 mg, which is consistent with similar reports (Obermann 2019, Omoregie & Okoh, 2015, Bendtsen et al, 2019. We found that those patients who had history tooth extraction required a higher dose of carbamazepine compared to those without a history of tooth extraction.…”
Section: Association Between Treatment Satisfaction Level and Gendersupporting
confidence: 87%
“…Trigeminal neuralgia, or tic douloureux, is chronic, episodic, and recurrent. It is a neuralgic pain that at best is distracting and at worst totally debilitating and disabling [ 22 , 23 ]. Pain originates in the trigeminal nerve complex or its territory.…”
Section: Discussionmentioning
confidence: 99%
“…Pain originates in the trigeminal nerve complex or its territory. It is caused by compression of the nerve root by vessels in the posterior fossa in 80–90% of cases [ 22 , 23 , 24 ], but it can be secondary to a number of other conditions to be mentioned shortly. The vessel most commonly compressing the trigeminal nerve root is the superior cerebellar artery (SCA), as identified by high-resolution 3 T magnetic resonance imaging (MRI).…”
Section: Discussionmentioning
confidence: 99%
“…TN surgical management is either non-ablative, which consists of the decompression of the nerve, preserving its normal function or ablation, which results in the destruction of sensory function of the trigeminal nerve. Some features are briefly discussed here including the main surgical options, but detailed indications and more information on the surgical procedures may be found in guidelines and have been reviewed by others [ 111 , 134 , 135 ].…”
Section: Treatmentmentioning
confidence: 99%
“…up to several weeks) and a high rate of pain recurrence compared to MVD. The most frequent complications reported are paraesthesias and facial numbness [ 135 , 140 , 141 ].…”
Section: Treatmentmentioning
confidence: 99%